Modeling of energy efficiency in heterogeneous network - Abdulkafi A.A.; Tiong S.K.; Chieng D.; Ting A.; Ghaleb A.M.; Koh J. (Maxwell Science Publications, 2023)
Cellular networks are undergoing transformation from conventional homogeneous macro Base Stations (BSs) to Heterogeneous Network (HetNet). This new paradigm not only offers a significant improvement in the overall network capacity or user data rate; it also promises an improvement in the overall network Energy Efficiency (EE). In this study, a theoretical model for evaluating the EE in HetNet is developed. A HetNet generally consists of different types of Base Stations (BSs) which operate in harmony towards a set of common goals defined by the network operator such as coverage and capacity improvement. Each BS may differ in terms of transmit power, achievable data rate, coverage, BS density and EE, under different network deployment scenarios. The results show that the picocell strongly impacts the Energy Efficiency (EE) of the HetNet as compared to microcell. More specifically it is observed that certain ratios of microcells and picocells per macro BS will result in sub-optimal of Area Energy Efficiency (AEE). It is shown that the AEE of HetNet also increases as the percentage area of macro BS overlaid by smaller cells and the density of micro/picocells increases. Maxwell Scientific Organization, 2013.